1977
DOI: 10.1172/jci108875
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gastrin, gastric inhibitory polypeptide, secretin, and the octapeptide of cholecystokinin upon immunoreactive somatostatin release by the perfused canine pancreas.

Abstract: A B S T R A C T The effects ofgastrin, gastric inhibitory polypeptide, secretin, and the octapeptide of pancreozymin-cholecystokinin on immunoreactive somatostatin release were studied in the isolated perfused dog pancreas. Gastrin at a concentration of 65 ng/ml and the octapeptide of pancreozymin-cholecystokinin at a c.oncentration of 25 ng/ml produced a prompt, but transient statistically significant, twofold rise in mean somatostatin concentration. Secretin at a concentration of 0.3 U/ml and gastric inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
1

Year Published

1981
1981
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(37 citation statements)
references
References 25 publications
(25 reference statements)
6
30
0
1
Order By: Relevance
“…By definition, incretin hormones are released in response to nutrient ingestion and stimulate pancreatic ␤-cells at their typical postprandial concentrations, especially in the presence of elevated plasma glucose concentrations (2,21). Such properties have been ascribed to GIP (22)(23)(24) and cholecystokinin (shown only in dogs and rodents) (25,26). According to this strict definition, GLP-1 would apparently not fulfill the criteria for an incretin hormone in the setting of the present experiments because it reduced rather than stimulated postprandial insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…By definition, incretin hormones are released in response to nutrient ingestion and stimulate pancreatic ␤-cells at their typical postprandial concentrations, especially in the presence of elevated plasma glucose concentrations (2,21). Such properties have been ascribed to GIP (22)(23)(24) and cholecystokinin (shown only in dogs and rodents) (25,26). According to this strict definition, GLP-1 would apparently not fulfill the criteria for an incretin hormone in the setting of the present experiments because it reduced rather than stimulated postprandial insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we wished to investigate how blocking of delta cell action might influence the effect of GIP and glucose on glucagon secretion, given the fact that GIP and glucose, like GLP-1, have been reported to stimulate pancreatic somatostatin secretion [28][29][30][31][32]. As a model, we used the isolated perfused rat pancreas, in which the integrity of the islet's cytoarchitecture and microvasculature is preserved, which is crucial when investigating paracrine interactions between islet cells.…”
Section: Introductionmentioning
confidence: 99%
“…And in a Starling Review, it is only fitting to mention that secretin was shown to be a powerful stimulator of the secretion of pancreatic somatostatin in a perfused dog pancreas preparation (Ipp et al 1977).…”
Section: Somatostatinmentioning
confidence: 99%